Chinese Business Groups in Hong Kong and Political Change in South China 1900-1925 - Chung, S. author. aut Link
XX, 188 p.
Keywords: Politics can be a profitable business as can be found in Republican era Canton amidst a politically fragmented China. Competing merchant groups in Hong Kong sought to finance the regional Canton government in return for financial concessions. This patronage system made commercial endeavours dependent on politics and embedded business in politics.